Testosterone replacement therapy and hospitalization rates in men with COPD. (14th November 2018) - Baillargeon, Jacques; Urban, Randall James; Zhang, Wei; Zaiden, Mohammed Fathi; Javed, Zulqarnain; Sheffield-Moore, Melinda; Kuo, Yong-Fang; Sharma, Gulshan
Testosterone deficiency is common in men with chronic obstructive pulmonary disease (COPD) and may exacerbate their condition. Research suggests that testosterone replacement therapy (TRT) may have a beneficial effect on respiratory outcomes in men with COPD. To date, however, no large-scale nationally representative studies have examined this association. The objective of the study was to assess whether TRT reduced the risk of respiratory hospitalizations in middle-aged and older men with COPD. We conducted two retrospective cohort studies. First, using the Clinformatics Data Mart—a database of one of the largest commercially insured populations in the United States—we examined 450 men, aged 40–63 years, with COPD who initiated TRT between 2005 and 2014. Second, using the national 5% Medicare database, we examined 253 men, aged ≥66 years, with COPD who initiated TRT between 2008 and 2013. We used difference-in-differences (DID) statistical modeling to compare pre- versus post-respiratory hospitalization rates in TRT users versus matched TRT nonusers over a parallel time period. DID analyses showed that TRT users had a greater relative decrease in respiratory hospitalizations compared with nonusers. Specifically, middle-aged TRT users had a 4.2% greater decrease in respiratory hospitalizations compared with nonusers (−2.4 decrease vs. 1.8 increase; p = 0.03); and older TRT users had a 9.1% greater decrease in respiratory hospitalizations compared with nonusers (−0.8 decrease vs. 8.3 increase; p = 0.04). These findings suggest that TRT may slow disease progression in patients with COPD. Future studies should examine this association in larger cohorts of patients, with particular attention to specific biological pathways.